Periconception and First Trimester Diet Modifies Appetite, Hypothalamic Gene Expression, and Carcass Traits in Bulls - Copping, Katrina J.; Callaghan, Matthew J.; Geesink, Geert H.; Gugusheff, Jessica R.; McMillen, I. Caroline; Rodgers, Raymond J.; Muhlhausler, Beverly S.; Vithayathil, Mini A.; Perry, Viv E. A. (Frontiers in Genetics, 2021)
Nulliparous yearling beef heifers (n = 360) were used to evaluate the effects of maternal dietary protein during the periconception and first trimester periods on postnatal growth, feedlot performance, feed intake and carcass characteristics of their male progeny. Heifers were individually fed 1.18 g crude protein (CP)/day (HPeri) or 0.62 g CP/day (LPeri) beginning 60 days before conception. From 24 to 98 days post-conception, half of each treatment group changed to the alternative post-conception diet and were fed 1.49 g CP/day (HPost) or 0.88 g CP/day (LPost) yielding four treatment groups in a 2 x 2 factorial design. From d 98 of gestation, heifers received a common diet until parturition. Calves were weaned at 183 days and developed on pasture before feedlot entry. Among the singleton non-castrated male progeny there were no differences between treatment groups in milk intake, pre- and post-weaning body weight, average daily gain and height (P > 0.05). Bulls underwent a 70 d Residual Feed Intake feedlot test commencing at 528 days of age. Feedlot entry and final body weight, feedlot average daily gain and Residual Feed Intake were not different (P > 0.05). Progeny of dams that had a change in diet [LPeri/HPost and HPeri/LPost] had 9% higher daily dry matter intake during the Residual Feed Intake test (P < 0.05) than progeny of dams that received low diet throughout both the peri-conception period and first trimester [LPeri/LPost ]. Further, mRNA expression of the appetite-stimulating agouti-related protein was increased in the arcuate nucleus of High Peri/LPost bulls (P < 0.05). At slaughter, progeny hot carcass weight was not different among bulls (P > 0.05), however carcass dressing percentage, estimated retail beef yield and Longissimus dorsi muscle cross sectional area were all higher for bulls from HPost dams (P < 0.05). This study highlights opportunities for the livestock industry whereby maternal dietary supplementation may be used to alter feed intake, enhance progeny muscling and alter fat deposition leading to improvement in efficiency of meat production in beef cattle.